A hiding in the lining: painful pericardial cyst. (22nd April 2013) - Masood, Abdul-Mannan; Ali, Omair M; Sequeira, Reginald
Abstract : A pericardial cyst is a rare and benign congenital malformation, usually discovered in the third or fourth decade of life. Its clinical presentation is variable, as it may be asymptomatic or present with chest pain, shortness of breath, or rarely with cardiac tamponade and arrhythmias. We present an interesting case of a woman presenting with chest pain who was found to have a pericardial cyst.